If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = 3(x + 2) + 3 Reorder the terms: -18 = 3(2 + x) + 3 -18 = (2 * 3 + x * 3) + 3 -18 = (6 + 3x) + 3 Reorder the terms: -18 = 6 + 3 + 3x Combine like terms: 6 + 3 = 9 -18 = 9 + 3x Solving -18 = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -18 + -3x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -18 + -3x = 9 + 0 -18 + -3x = 9 Add '18' to each side of the equation. -18 + 18 + -3x = 9 + 18 Combine like terms: -18 + 18 = 0 0 + -3x = 9 + 18 -3x = 9 + 18 Combine like terms: 9 + 18 = 27 -3x = 27 Divide each side by '-3'. x = -9 Simplifying x = -9
| 10x+18=158 | | 2(5x+2)+1=-5 | | -21=3(4x+5) | | 5(3x+4)=5x+10 | | -35=5(3x-1) | | 2e-8f+6e+3f= | | 25=5(2x-5) | | 5(2x-5)=25 | | 3(5x-5)-9=36 | | 4(2x-5)+6=-46 | | 3(3x+2)=3x-36 | | -12=3(x+5) | | 3b-4a-(2b+a)= | | 5x+26=5(5x-3)+1 | | 6(1-2x)-3(x+1)= | | -x-6=7x-62 | | 7h-26=23 | | 4(2x+2)=-x-10 | | 4x+1=3(x-5)+5 | | 4=4(x+4) | | -5x-7=-3x-33 | | 4(x-5)=-2x-2 | | -x+28=-4x+49 | | -11x+34=-5x+64 | | 2(x+4)+9=29 | | 22=3(3x+3)+4 | | -2x-1=5(4x+5)-4 | | x+34=5(x+1)-3 | | -8x+20=-2x+44 | | 9m-11=61 | | 5x+33=4(3x-3)+3 | | -3.4q=-4.6-1.1q |